EFEKTIVITAS PEMBERIAN NUGGET PATAKE TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL - Sukati Sarmin; Warda Anil Masyayih; Asri Fitri Yati (JOMIS (Journal of Midwifery Science), 2026)
The incidence of anemia in pregnant women in Indonesia is still quite high. Approximately 95% of anemia cases are caused by iron deficiency. During pregnancy, anemia ranks second among causes of maternal mortality, at around 12.8%, after postpartum hemorrhage. One effective strategy to overcome anemia during pregnancy is to consume 90 Fe tablets continuously. This study aims to assess the effectiveness of consuming PATAKE nuggets consisting of catfish, tofu, and moringa leaves on increasing hemoglobin levels in pregnant women. This type of research is quantitative with a quasi-experimental design - two groups pretest and posttest. The collected data consisted of primary data, namely the assessment of hemoglobin levels of pregnant women and secondary data obtained from KIA books and medical records. This study consisted of 50 respondents and were divided into two groups: a control group of 25 respondents who were only given Fe tablets and an intervention group consisting of 25 respondents who were given PATAKE nuggets, each given for 14 days and then evaluated. Statistical analysis used t-dependent and t-independent. The average hemoglobin level in the control group before the intervention was 9.36 gr/dL, increasing to 11.6 gr/dL after the intervention. Meanwhile, during the pretest, the hemoglobin level in the intervention group was 9.36 gr/dL, then increased to 12.0 gr/dL during the posttest. Iron supplements and PATAKE nuggets had a significant impact on increasing hemoglobin levels in both groups, with a p value = 0.000 (<α0.05). Meanwhile, the results of the independent t-test comparing the control and intervention groups during the posttest showed a p value = 0.002 (<α0.05), indicating a difference in the average hemoglobin levels between the control and intervention groups. The results of this study are expected to be food commodification for daily menu variations accompanying Fe tablets